Artemisinin upregulates neural cell adhesion molecule L1 to attenuate neurological deficits after intracerebral hemorrhage in mice - Jianjiang Wang; Jie Yin; Xi Zheng (Brain and Behavior, 2022)
Abstract Background and purpose Intracerebral hemorrhage (ICH) is a subtype of stroke and results in neurological deficits in patients without any effective treatments. Artemisinin (ART), a well‐known antimalarial Chinese medicine, exerts multiple essential roles in the central and peripheral nervous system due to its antioxidative and anti‐inflammation properties. Neural cell adhesion molecule L1 (L1CAM, L1) is considered to be implicated in neural development, functional maintenance, and neuroprotection during disease. However, whether these two essential molecules are neuroprotective in ICH remains unclear. Methods Therefore, the present study investigated the influence of ART on the recovery of neurological deficits in a mouse model of ICH induced by collagenase and the underlying mechanism. Results It was revealed that ART is capable of upregulating L1 expression to alleviate brain edema, reduce oxidative stress, and inhibit inflammation to alleviate ICH‐induced brain injury to improve the neurological outcome in mice suffering from ICH. Conclusion These results may lay the foundation for ART to be a novel candidate treatment for ICH.